The radiopacity of glass ionomer cement after addition of nHA powder: experimental study - Lusi Hidayati; Supriyadi Supriyadi; Dea Azalia Annisa; Sulistiyani Sulistiyani; Raditya Nugroho; Cortino Sukotjo (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: One of the restorative materials often used in dental restoration treatment is GIC. One type of GIC is conventional GIC. Conventional GIC has the disadvantage of having low compressive strength compared to resin-modified GIC and high viscosity. One of the efforts to improve the mechanical properties of GIC is by adding nano hydroxyapatite (nHA) which can be obtained from natural materials such as eggshells. The addition of nHA to GIC can increase the compressive strength of GIC and the addition of nHA is thought to result in a change in the radiopacity properties of GIC. The research aims to analyze the radiopacity of GIC after the addition of nano-hydroxyapatite powder. Methods: The number of samples was 24 discs with a diameter of 7 mm and a height of 3 mm which were divided into 4 group. The research group was K0 (GIC) as the control group, K1 (GIC+ 2% nHA), K2 (GIC+ 3% nHA), and K3 (GIC + 4% nHA). Radiopacity measurements were carried out using the J Image application. Results: The results of the ANOVA test was p<0.05, which means that the radiopacity values in each group had a significant difference. The average gray value of GIC without the addition of nHA (K0) was 206.5, GIC + 2% nHA (K1) was 233.0, GIC + 3% nHA (K2) was 237.8 and GIC + 4% nHA (K3) was 241.0 measured with Image J. Conclusions: The addition of nHA powder can increase the radiopacity of GIC and 4% nHA powder added to GIC has the highest radiopacity value compared to 2 and 3% nHA powder added to GIC.  .Key words radiopacity, glass ionomer, cement, nHARadiopasitas glass ionomer kaca setelah penambahan bubuk nHA: studi eksperimentalAbstrakPendahuluan: Salah satu bahan restoratif yang sering digunakan dalam perawatan restorasi gigi adalah GIC. Salah satu jenis GIC adalah GIC konvensional. GIC konvensional memiliki kekurangan yaitu kekuatan tekannya rendah dibandingkan dengan GIC yang dimodifikasi resin dan viskositas tinggi. Salah satu upaya untuk meningkatkan sifat mekanik GIC adalah dengan menambahkan nanohidroksiapatit (nHA) yang dapat diperoleh dari bahan alami seperti cangkang telur. Penambahan nHA ke GIC dapat meningkatkan kekuatan tekan GIC dan penambahan nHA diduga mempengaruhi sifat radiopasitas GIC. Penelitian ini bertujuan untuk mengetahui radiopasitas GIC setelah penambahan bubuk nanohidroksiapatit. Metode: Jumlah sampel adalah 24 cakram dengan diameter 7 mm dan tinggi 3 mm yang dibagi menjadi 4 kelompok. Kelompok penelitian ini adalah K0 (GIC) sebagai kelompok kontrol, K1 (GIC+2% nHA), K2 (GIC+3% nHA), dan K3 (GIC+4% nHA). Hasil: Hasil uji ANOVA diperoleh nilai p<0.05 yang berarti bahwa nilai radiopasitas pada setiap kelompok memiliki perbedaan yang signifikan. Rata-rata nilai gray value GIC tanpa penambahan nHA (K0) adalah 206,5, GIC + 2% nHA (K1) adalah 233,0, GIC + 3% nHA (K2) adalah 237,8 dan GIC + 4% nHA (K3) adalah 241,0. Simpulan: Penambahan bubuk nHA dapat meningkatkan radiopasitas GIC dan 4% bubuk nHA yang ditambahkan ke GIC memiliki nilai radiopasitas tertinggi dibandingkan dengan 2 dan 3% bubuk nHA yang ditambahkan ke GIC.Kata kunciradiopasitas, semen, glass  ionomer, nanohidroksiapatit